TP53 Gene Status Affects Survival in Advanced Mycosis Fungoides - Wooler, Gitte; Melchior, Linea; Ralfkiaer, Elisabeth; Rahbek Gjerdrum, Lise Mette; Gniadecki, Robert (Frontiers in Medicine, 2016)
TP53 is frequently mutated in different types of neoplasms including leukemia and lymphomas. Mutations of TP53 have also been reported in mycosis fungoides (MF), the most common type of cutaneous lymphoma. However, little is known about the frequency, spectrum of mutations and their prognostic significance in MF. In this study we have optimized the protocol for Sanger sequencing of TP53 using DNA extracted from archival paraffin-embedded biopsies. Of 19 samples from patients with stage IIB MF or higher, 31% harboured mutations in TP53. Overall survival of the patients with mutated TP53 was significantly shorter than median survival in the age- and stage-matched patients treated in our Institution. Distribution of mutations was heterogenous in TP53 exons, however C>T transitions were common suggesting the causal role of ultraviolet radiation. We propose that TP53 mutation status would be useful for risk stratification of patients with advanced MF.